2018
DOI: 10.1680/jadcr.17.00198
|View full text |Cite
|
Sign up to set email alerts
|

Phase evolution of slag-rich cementitious grouts for immobilisation of nuclear wastes

Abstract: An updated calcium silicate hydrate (C–S–H) model incorporating aluminium-containing end-members was used for thermodynamic modelling of blended cements using blast-furnace slag and Portland cement (BFS:PC) with ratios of 1:1, 3:1 and 9:1, using GEMSelektor. Selective dissolution and magic angle spinning nuclear magnetic resonance (MAS NMR) studies were performed to determine the degree of hydration (DoH) of the anhydrous material as an input parameter for the modelling work. Both techniques showed similar res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 76 publications
0
16
0
Order By: Relevance
“…The sulfate content of the BFS:PC systems will only increase if both the degree of hydration (DoH) of BFS increases and there is a sufficiently oxidising environment to convert the released sulfide to sulfate. Prentice et al [33] found the DoH in Sellafield Ltd specification 3:1 BFS:PC system to be between 50-55% for BFS after one year, with alite and belite hydration at 85% and 53% respectively. There was no intermixing of Calumite® with the GGBS fraction in the Prentice study, and the larger particle size of the Calumite® component will reduce the degree of reaction in the current study; Sanderson et al found the behaviour of Calumite® to be similar to an inert filler [34].…”
Section: Phase Assemblagementioning
confidence: 99%
See 2 more Smart Citations
“…The sulfate content of the BFS:PC systems will only increase if both the degree of hydration (DoH) of BFS increases and there is a sufficiently oxidising environment to convert the released sulfide to sulfate. Prentice et al [33] found the DoH in Sellafield Ltd specification 3:1 BFS:PC system to be between 50-55% for BFS after one year, with alite and belite hydration at 85% and 53% respectively. There was no intermixing of Calumite® with the GGBS fraction in the Prentice study, and the larger particle size of the Calumite® component will reduce the degree of reaction in the current study; Sanderson et al found the behaviour of Calumite® to be similar to an inert filler [34].…”
Section: Phase Assemblagementioning
confidence: 99%
“…Given the estimated range of DoH, the concentrations are not anticipated to vary significantly without oxidation of the sulfide (Table 5). Thermodynamic modelling of similar systems (unirradiated) [33] predicts ettringite to be replaced by monosulfoaluminate in the phase assemblage by 28 days; monosulfoaluminate and hemicarboaluminate were predicted to be the major AFm components. The persistence of ettringite together with AFm phases can be seen in the XRD data for the BFS:PC control samples (Figure 8), indicating the sulfate had not decreased as predicted.…”
Section: Phase Assemblagementioning
confidence: 99%
See 1 more Smart Citation
“…[11,12]. Also, alkaline cements are characterized by the ability to fix in their structure the elements of radioactive and heavy metals not only on the physical, but also on the chemical level [13].…”
Section: Research Of Existing Solutions Of the Problemmentioning
confidence: 99%
“…The chemistry of slag-derived binders is strongly influenced by the selection of the 9 activator [8][9][10]. The main reaction product of slag-blended PC is C-A-S-H gel, while the formation of secondary phases depends on the slag:PC ratio; increasing the slag content in slag-PC blends leads to a decrease in portlandite and ettringite content, and an increase in hydrotalcite [11,12]. Alkali-containing C-A-S-H (often represented as C-(N-)A-S-H using Na as the archetypal alkali metal) is the main reaction product in alkali-activated slag binders [13].…”
mentioning
confidence: 99%